Digitalisasi Supervisi Akademik dan Evaluasi Kinerja Guru Berbasis Mobile di Sekolah Menengah Pertama - Az Zahra Lishani Salsabila; Muhammad Adri; Dedy Irfan; Khairi Budayawan (TIN: Terapan Informatika Nusantara, 2026)
The effectiveness of academic supervision in middle schools is often hindered by delayed feedback loops due to inefficient conventional data management. This study aims to develop a mobile-based academic supervision and teacher performance evaluation digitalization system at SMP Pembangunan Laboratorium UNP, integrating three pillars of oversight: leadership supervision, teacher self-reflection, and authentic student evaluation. Using the Waterfall development method, this study involved the principal, vice-principal of curriculum, administrative staff, teachers, and student representatives as respondents. Functional validation was conducted using blackbox testing techniques to ensure all modules operate consistently according to requirements specifications. The results indicate that the integration of oversight modules into a Flutter and MySQL-based mobile platform significantly reduces data recapitulation time, from days to real-time data presentation. The substantial findings of this study emphasize that digitalization can strengthen transparency and accountability in teacher performance assessment objectively. The practical implication of this system is the creation of a data-driven educator professionalism culture, where feedback for improving teaching quality can be received instantaneously to continuously enhance the quality of learning.